Functional expression of KCNQ (Kv7) channels in guinea pig bladder smooth muscle and their contribution to spontaneous activity. (21st June 2013) - Anderson, U A; Carson, C; Johnston, L; Joshi, S; Gurney, A M; McCloskey, K D
<x xml:space="preserve">Abstract</x> Background and Purpose The aim of the study was to determine whether KCNQ channels are functionally expressed in bladder smooth muscle cells (SMC) and to investigate their physiological significance in bladder contractility. Experimental Approach KCNQ channels were examined at the genetic, protein, cellular and tissue level in guinea pig bladder smooth muscle using RT‐PCR, immunofluorescence, patch‐clamp electrophysiology, calcium imaging, detrusor strip myography, and a panel of KCNQ activators and inhibitors. Key Results KCNQ subtypes 1–5 are expressed in bladder detrusor smooth muscle. Detrusor strips typically displayed TTX‐insensitive myogenic spontaneous contractions that were increased in amplitude by the KCNQ channel inhibitors XE991, linopirdine or chromanol 293B. Contractility was inhibited by the KCNQ channel activators flupirtine or meclofenamic acid (MFA). The frequency of Ca2+‐oscillations in SMC contained within bladder tissue sheets was increased by XE991. Outward currents in dispersed bladder SMC, recorded under conditions where BK and KATP currents were minimal, were significantly reduced by XE991, linopirdine, or chromanol, and enhanced by flupirtine or MFA. XE991 depolarized the cell membrane and could evoke transient depolarizations in quiescent cells. Flupirtine (20 μM) hyperpolarized the cell membrane with a simultaneous cessation of any spontaneous electrical activity. Conclusions and Implications These novel findings reveal the role of KCNQ currents in the regulation of the resting membrane potential of detrusor SMC and their important physiological function in the control of spontaneous contractility in the guinea pig bladder.